IMPLEMENTASI KEBIJAKAN TENTANG DISIPLIN PEGAWAI NEGERI SIPIL PADA DINAS PENDAPATAN, PENGELOLAAN KEUANGAN DAN ASET DAERAH KOTA PALU - Hafid, Abdul (Katalogis, 2016)
This study aims to analyze the implementation of civil servant discipline policy at Palu City Department of Revenue and Financial and Asset Management. This study uses qualitative method. The location of this research was the office of Palu City Department of Revenue and Financial and Asset Management. The informants in this study were selected by using purposive method, i.e. informant selection with certain considerations to assign 6 informants. Data were collected through observations, interviews, and documentations. In this study, the researcher used the approach of Miles and Hubermen interpretation analysis, to bring up what the meanings of the problems, cases, conditions, or circumstances, that were studied.The results of this study show that: 1. Communication via transmission: clarity and consistence had not been good. 2. Resources: civil servant resources were adequate, while budgetary resources were not specifically budgeted. 3. Disposition: it had not run as it should. 4. Bureaucratic structure: it was implemented fairly well because there had been operational standards and procedures.